PENGEMBANGAN BAHAN AJAR BUKU SAKU DIGITAL PADA MATERI PELAYANAN PRIMA KELAS X BISNIS DIGITAL : STUDI KASUS PADA EDUCAFE DI SMK NEGERI 1 JOMBANG - Wirainata, Amanda; Sudarwanto, Tri; Saino, Saino; Irawati, Winaika (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
This study aims to develop and test the feasibility of a digital pocket book as an open material on Excellent Service material for class X Digital Business students of SMK Negeri 1 Jombang. The development uses the AADIE model. The process begins with a needs analysis and initial review by media, material, and language experts, followed by validation using the BSNP instrument. The validation results show that the digital pocket book has a very high level of feasibility, namely 94% by media experts, 95% by material experts, and 96% by language experts. The trial was conducted in two stages, namely small groups (10 students) and field tests (90 students). The trial results showed a very positive student response with an average practicality percentage of 95%. The digital pocket book is considered easy to use, relevant to practice at Educafe, and able to increase student motivation and understanding. Thus, this digital pocket book is declared very feasible to be used as an alternative contextual open material that supports project-based learning in vocational schools.